The Anti-mycobacterial Activity of a Diterpenoid-Like Molecule Operates Through Nitrogen and Amino Acid Starvation - Crusco, Alessandra; Baptista, Rafael; Bhowmick, Sumana; Beckmann, Manfred; Mur, Luis A. J.; Westwell, Andrew D.; Hoffmann, Karl F. (Frontiers in Microbiology, 2019)
A library of 14 nontoxic diterpenoid-like compounds (CC50 > 70 µM on HepG2 human liver cells) was screened against Mycobacterium smegmatis, Staphylococcus aureus and Escherichia coli to determine antimicrobial activity. Some compounds with a phenethyl alcohol core substituted with a β-cyclocitral derivative demonstrated anti-mycobacterial activity, with the most active being compound 1 (MIC = 23.4 mg/L, IC50 = 0.6 mg/L). Lower activity was exhibited against S. aureus, while no activity was displayed against E. coli. Low cytotoxicity was confirmed on HepG2 cells and newly derived for RAW 264.7 murine macrophages (SI > 38). The sub-lethal (IC50 at 6 h) effect of compound 1 on M. smegmatis was examined through untargeted metabolomics and compared to untreated bacteria and bacteria treated with sub-lethal (IC50 at 6 h) concentrations of the antituberculosis drugs ethambutol, isoniazid, kanamycin and streptomycin. The study revealed that compound 1 acts differently from the reference antibiotics and that it significantly affects amino acid, nitrogen, nucleotides and folate-dependent one-carbon metabolism of M. smegmatis, giving some insights about the mode of action of this molecule. A future medicinal chemistry optimization of this new anti-mycobacterial core could lead to more potent molecules.